CLINICAL SIGNIFICANCE OF ASSESSMENT OF THROMBOSPONDIN AND PLACENTA GROWTH FACTOR LEVELS IN PATIENTS WITH SICKLE CELL ANEMIA: TWO CENTERS EGYPTIAN STUDIES - adel abd elhaleim hagag; Ghada Elmashad; Aml Ezzat Abd El-Lateef (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract: Background: Sickle cell disease has a worldwide distribution. Vaso-occlusive crisis (VOC) is one of the most important clinical features of the disease. Thrombospondin (TSP1) and Placenta growth factor (PlGF) have been reported to be involved in sickle cell diseases (SCD). Objective: The aim of this study is to assess TSP1 and PlGF levels in SCD patients. Patients and methods: This study was carried out in forty patients with sickle cell anemia who were attendants to Hematology units, Pediatric Departments, Tanta and Elmenofia University Hospital in the period between December 2011 and December 2013 including twenty patients with sickle cell anemia during vaso-occlusive crisis (twelve males and eight females) and twenty patients with sickle cell disease out of crisis (ten males and ten females). Also this study included twenty healthy children of matched age and sex as a control group. Serum TSP1 and PlGF levels were analyzed by ELISA. Results: Mean serum TSP1 levels were significantly higher in SCA patients with crisis than SCA patients out of crisis and were significantly higher in SCA patients with or without crisis compared to controls. Mean serum Placenta growth factor levels were significantly higher in SCA patients with crisis than SCA patients out of crisis and were significantly higher in SCA patients with or without crisis compared to controls. Conclusions: TSP1and PlGF concentration may be useful VOC markers in SCD patients. Recommendation: Further studies should be conducted to determine the exact point before VOC, when serum TSP1 and PIGF levels begin to increase. This requires monitoring of the TSP1 and PIGF levels in sickle cell patients out of crisis, showing how rapidly these levels increase just before VOC development.